A novel smart supramolecular organic gelator exhibiting dual-channel responsive sensing behaviours towards fluoride ion via gel–gel states. Issue 25 (19th May 2016) - Mehdi, Hassan; Pang, Hongchang; Gong, Weitao; Dhinakaran, Manivannan Kalavathi; Wajahat, Ali; Kuang, Xiaojun; Ning, Guiling
Abstract : A smart organic gelatorG-16 showed robust gelation as organogelOG and metallogelOG-Zn . BothOG andOG-Zn exhibited different sensing mode towards F − .OG-Zn displayed unique selectivity for F − and formedOG-Zn-F gel whileOG selectively formedOG-F gel via AIE. Abstract : A novel smart supramolecular organic gelatorG-16 containing anion and metal-coordination ability has been designed and synthesized. It shows excellent and robust gelation capability as a strong blue fluorescent supramolecular organic gelOG in DMF. Addition of Zn 2+ produced Zn 2+ -coordinated supramolecular metallogelOG-Zn . Organic gelOG and organometallic gelOG-Zn exhibited efficient and different sensing behaviors towards fluoride ion due to the variation in self-assembling nature. Supramolecular metallogelOG-Zn displayed specific selectivity for fluoride ion and formedOG-Zn-F with dramatic color change from blue to blue green in solution and gel to gel states. Furthermore after directly addition of fluoride intoOG produced fluoride containing organic gelOG-F with drastically modulation in color from blue to greenish yellow fluorescence via strong aggregation-induced emission (AIE) property. A number of experiments were conducted such as FTIR, 1 H NMR, and UV/Vis spectroscopies, XRD, SEM and rheology. These results revealed that the driving forces involved in self-assembly ofOG, OG-Zn, OG-Zn-F andOG-F were hydrogen bonding, metal coordination, π–π interactions, and van der Waal forces. In contrast to the most anion responsive gels, particularly fluoride ion responsive gels showed gel–sol state transition on stimulation by anions, the gel state ofOG andOG-Zn did not show any gel-to-sol transition during the whole F − response process.